Fishery co-management : - Pomeroy, Robert S. (Cambridge, MA, 2006)
This handbook describes the process of community-based co-management from its beginning, through implementation, to turnover to the community. It provides ideas, methods, techniques, activities, checklists,examples, questions and indicators for the planning and implementing of a process of community-based co-management. It focuses on small-scale fisheries (freshwater, floodplain, estuarine, or marine) in developing countries, but is also relevant to small-scale fisheries in developed countries and to the management of other coastal resources (such as coral reefs, mangroves, sea grass, and wetlands). This handbook will be of significant interest to resource managers, practitioners, academics and students of small-scale fisheries